Perspektif Pandangan Iman Kristiani Terhadap Filsafat Okultisme: Hermitisisme dan Kabbalah - Lesmana, Yeffry hendra (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Kabbalah and Hermitism are often unwittingly adopted into the practice of Christian theology due to the clergy's ignorance of this occult philosophical knowledge. The practice of occult philosophy sometimes unconsciously enters into the social practice of Christian society, especially those that are thick with local culture. The concept of cultural inculturation is a legitimization that is often used as an excuse to announce the practice. The purpose of this writing is to provide theological thinking insights into the philosophical practices of the Kabbalah occult and Hermitism so that the church returns to the true teachings and is based on the principles of the Christian faith. This research method uses a qualitative method based on literature research, observation of social conditions, community culture, and history. The results of the study show that the practices of Philosophy, Kabbalah Occultism and Hermitism inadvertently inculturate the socio-pastoral conditions of the Christian faith, which also has an impact on legalized religious ritual actions.